(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
These sets of isotopic parameters basically fall into two broad groups based on their values. The values of the parameters of various sets in each group are quite similar to each other but distinctly different from those of the other group. These parameters are also related to the Rb-Sr isotopic parameters because the latter are partly derived from the Sm-Nd isotopic parameters. As for instance but for the correlation between 87Sr/86Sr and 143Nd/144Nd ratios of recent oceanic basalts the present-day 87Sr/86Sr ratio couldnt be determined. So the most apt or plausible set of Sm-Nd isotopic parameters has to be not only internally consistent but also has to be consistent with the Rb-Sr isotopic parameters. In this paper I have shown how to distinguish internally consistent sets of Sm-Nd isotopic parameters and then how to pick up the one from those which is consistent with the Rb-Sr isotopic parameters as well. The one test of the internal consistency is that in which the measured present-day Nd isotope ratio matches very closely with the one computed from the other reference values. Then from the internally consistent sets, the one which is also consistent with the Rb-Sr isotopic parameters is considered to be the most plausible set of Sm-Nd isotopic parameters. The values of parameters are, 0.50677, 0.512636, and 0.1936 for the initial 143Nd/144Nd ratio, the present-day 143Nd/144Nd and the present-day 147Sm/144Nd ratios, respectively.